Longitudinal Links between Older Sibling Features and Younger Siblings’ Academic Adjustment during Early Adolescence - Bouchey, Heather A. (2010)
This study investigated prospective relations between (1) older siblings’ support and academic engagement and (2) younger siblings’ academic adjustment from 7(th) to 8(th) grade. The study was unique in that it incorporated a sample of both African American and European American adolescents. Also investigated was the extent to which the gender constellation (same-sex vs. mixed-sex) of sibling dyads moderated prospective associations. Findings revealed that, in mixed-sex dyads only, younger siblings’ perceptions of support received from the older sibling and their positive image of the older sibling predicted declines in the younger sibling’s academic self-perceptions and performance over time, even after controlling for younger siblings’ background characteristics and support from parents. Older siblings’ reported support to younger siblings also predicted declines in younger siblings’ academic adjustment, whereas the older siblings’ own level of academic engagement predicted an increase in younger siblings’ academic adjustment over time. Overall, findings did not differ substantially for African and European American adolescents.